Building commercial partnerships for orange‐fleshed sweetpotato processing: Evidence and lessons for programming. - Muoki, Penina Ngusye; Kebaara, K. (International Potato Center, 2019)
The goal of the workshop was to gather insights on options for commercial partnerships and co‐investment in OFSP commercialization. The objectives were to: provide updates on introduction of commercially marketed processed products that use OFSP as a major ingredient; provide feedback on a qualitative study among actors involved in OFSP commercialization in Kenya, Malawi, and Rwanda; and to develop recommendations for partnerships and co‐investment in OFSP processing and marketing using participatory methods.